A new species of the hermit crab genus Areopaguristes Rahayu & McLaughlin (Crustacea, Decapoda, Anomura, Paguroidea, Diogenidae) from the Mexican Pacific - Ayón-Parente, Manuel; Hendrickx, Michel E. (Zootaxa, 2016)
A new species of hermit crab, Areopaguristes espetacioni, family Diogenidae, is described and illustrated in detail, including the color pattern in live/fresh specimens. This is the fifth species of Areopaguristes reported from the eastern Pacific. Given the morphological similarity between Areopaguristes espetacioni n. sp. and A. tudgei Lemaitre & Felder, 2012, these can be considered sister species. The presence of a long rostrum, the antennal flagella with short setae, chelipeds and ambulatories legs with dense plumose setae, and telson with calcareous teeth on the posterior margin allow to separate Areopaguristes espetacioni n. sp. from all other species in the genus previously described for the region. A key for Areopaguristes species from the eastern tropical Pacific is provided.